Green solutions for clean water: Natural materials in contaminant detection and removal - Mithra Geetha (14151807) (2025)
The growing crisis of global water contamination, fueled by rapid industrialization, urban development, and intensified agriculture, has created an urgent need for sustainable, efficient, and environmentally friendly water treatment technologies. Conventional treatment approaches often fall short due to high operational costs, potential secondary pollution, and limited effectiveness against emerging pollutants. In response, green and natural materials have emerged as attractive alternatives for both contaminant removal and water quality monitoring, offering advantages such as biodegradability, ecological safety, cost-efficiency, and wide availability. This review provides a detailed overview of recent advancements in utilizing plant-based adsorbents, agricultural and industrial bio-wastes, natural polymers, clays, algae, microbial biomass, and eco-friendly nanomaterials for water purification. It explores key removal strategies including adsorption, photocatalytic degradation, membrane filtration, bio-based coagulation-flocculation, and bioremediation, demonstrating their effectiveness in targeting heavy metals, organic pollutants, biological contaminants, microplastics, and newly recognized environmental toxins. Furthermore, the integration of these natural materials into portable, low-cost sensing technologies—such as colorimetric, electrochemical, and fluorescent biosensors—is examined, offering innovative tools for real-time contaminant detection. The review also highlights emerging hybrid systems that combine green nanomaterials with biochar, biopolymers, and metal-based nanoparticles to enhance contaminant removal and multifunctional performance. Key practical considerations, including scalability, material uniformity, environmental impacts, biodegradability, and regulatory challenges, are addressed. A life cycle assessment (LCA) perspective is incorporated to compare the sustainability of these green alternatives with conventional materials. The article concludes by outlining future research opportunities focused on hybrid technologies, smart sensing integration, and circular economy frameworks to support scalable, sustainable, and decentralized water purification solutions. Other Information Published in: Trends in Environmental Analytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.teac.2025.e00285